The Australian War Crimes Trials, 1945-51 - McCormack, T.; Morris, Narrelle (Brill Nijhoff, 2016)
This unique volume provides a detailed analysis of Australia’s 300 war crimes trials of principally Japanese accused conducted in the immediate aftermath of the Second World War.